Push-pull process for contact defect-free patterning in reverse offset printing. (22nd December 2016) - Kusaka, Yasuyuki; Sugihara, Kazuyoshi; Ushijima, Hirobumi
Abstract: Reverse offset printing is one of the most promising printing techniques for printed electronics because it enables us to generate fine patterns with high fidelity. However, in the pattern-generation process, where some of the ink applied on a blanket is removed by a cliché upon contact, there may be contact-defect formations due to unwanted contact between the bottom regions of the cliché and the blanket. This may occur when the pattern size is wide or when the depth of the cliché is shallow. To solve this problem, we develop a modified printing protocol that adopts a 'negative' printing pressure condition called a 'push-pull' process. In this process, the blanket first comes into contact with the cliché by pushing a blanket roller, and the roller is then pulled back to prevent the blanket indentation into the grooves of the cliché. By incorporating the push-pull process in reverse offset printing, we demonstrate defect-free formations of 4.0 mm × 5.0 mm large patterns using a shallow cliché with a depth of 2.6 μ m, which is unattainable with the conventional push-only process. Further, we show that the adhesion between the ink-coated blanket and the cliché contributes to the maintenance of the contact through the printing process, even in the pull situation.